2015
DOI: 10.1108/srj-08-2013-0093
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corporate social responsibility on firm risk

Abstract: Purpose – The purpose of this paper is to investigate the link between corporate social responsibility (CSR) and risk for a sample of US firms rated by KLD. Design/methodology/approach – The authors’ approach involves three distinctive features. First, the authors use individual indicators of CSR to highlight which CSR dimension matters most for a firm’s risk. Second, the authors distinguish CSR strengths and concerns to reveal potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 52 publications
7
62
2
5
Order By: Relevance
“…It means that companies maximize stakeholder's interests when firms have high CSR performance. However, several studies in the U.S. context find a positive direction on the effect of CSR and firm's risk (Ayadi et al, 2014;Nguyen and Nguyen, 2015). In other words, firms are riskier when they implement CSR.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It means that companies maximize stakeholder's interests when firms have high CSR performance. However, several studies in the U.S. context find a positive direction on the effect of CSR and firm's risk (Ayadi et al, 2014;Nguyen and Nguyen, 2015). In other words, firms are riskier when they implement CSR.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…They indicate that several CSR dimensions (e.g., employee relations, product characteristics, and diversity) are positively associated with risk taking. Nguyen and Nguyen (2015) show that U.S. firms with better CSR implementation experience higher company's risk. Based on the empirical evidence discussed, the findings on the association between CSR and company's risk are mixed and inconclusive, especially in emerging market context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also linked CSR to the risks facing the company. Some of these studies were conducted by Nguyen and Nguyen (2013), Lee (2016), Hsu and Chen (2015), Orlitzky and Benjamin (2001), Godfrey (2005), Sen et al (2006), and Melo (2012).…”
Section: Introductionmentioning
confidence: 99%
“…The work in [38][39][40] stated that positive CSR reduces the risk of companies, but [41] concluded that CSR strengths and concerns both increase company risk. The work in [8] found that ESG risks are not valued in stock markets, which leads to negative surprises when ESG incidents occur.…”
Section: Introductionmentioning
confidence: 99%